Multiscale and multimodal imaging for three-dimensional vascular and histomorphological organ structure analysis of the pancreas - Gabriel Alexander Salg; Verena Steinle; Jonas Labode; Willi Wagner; Alexander Studier-Fischer; Johanna Reiser; Elyes Farjallah; Michelle Guettlein; Jonas Albers; Tim Hilgenfeld; Nathalia A. Giese; Wolfram Stiller; et al. (Scientific Reports, 2024)
Abstract Exocrine and endocrine pancreas are interconnected anatomically and functionally, with vasculature facilitating bidirectional communication. Our understanding of this network remains limited, largely due to two-dimensional histology and missing combination with three-dimensional imaging. In this study, a multiscale 3D-imaging process was used to analyze a porcine pancreas. Clinical computed tomography, digital volume tomography, micro-computed tomography and Synchrotron-based propagation-based imaging were applied consecutively. Fields of view correlated inversely with attainable resolution from a whole organism level down to capillary structures with a voxel edge length of 2.0 µm. Segmented vascular networks from 3D-imaging data were correlated with tissue sections stained by immunohistochemistry and revealed highly vascularized regions to be intra-islet capillaries of islets of Langerhans. Generated 3D-datasets allowed for three-dimensional qualitative and quantitative organ and vessel structure analysis. Beyond this study, the method shows potential for application across a wide range of patho-morphology analyses and might possibly provide microstructural blueprints for biotissue engineering.